Causal associations of obstructive sleep apnea with Chronic Respiratory Diseases: a Mendelian Randomization study - Hong, Ping-Yang; Liu, Dong; Liu, Ang; Su, Xin; Zhang, Xiao-Bin; Zeng, Yi-Ming (BMC pulmonary medicine, 2024)
Purpose This study aimed to elucidate the causal relationship between Obstructive Sleep Apnea (OSA) and Chronic Respiratory Diseases (CRDs), employing Mendelian Randomization (MR) to overcome limitations inherent in observational studies. Methods Utilizing a two-sample MR approach, this study analyzed genetic variants as instrumental variables to investigate the causal link between OSA and various CRDs, including chronic obstructive pulmonary disease (COPD), asthma, bronchiectasis, and idiopathic pulmonary fibrosis (IPF). Data were sourced from the FinnGen Consortium (OSA, n = 375,657) and UK Biobank, focusing on genome-wide associations between single-nucleotide polymorphisms (SNPs) and the diseases. Instrumental variables were selected based on strict criteria, and analyses included a random-effects inverse-variance weighted method supplemented by several sensitivity analyses. Results The study suggests a protective effect of OSA against COPD (OR = 0.819, 95% CI 0.722–0.929, P-value = 0.002), which becomes non-significant after adjusting for BMI, indicating a potential mediating role of BMI in the OSA-COPD nexus. No significant causal links were found between OSA and other CRDs (asthma, IPF, bronchiectasis) or between COPD, asthma, and OSA. Conclusions Our findings reveal a BMI-mediated protective effect of OSA on COPD, with no causal connections identified between OSA and other CRDs. These results emphasize the complex relationship between OSA, BMI, and COPD, guiding future clinical strategies and research directions, particularly in light of the study’s genetic analysis limitations.